Chemical Constituents and in Vitro/In Vivo Pharmacological Effects of Mentha piperita L. Essential oil in Different Regions of Algeria - Halli, Latifa; Harchaoui, Lilya; Messaoudi, Mohammed; Dahmane, Thoraya; Aid, Fatiha; Sawicka, Barbara; Zahnit, Wafa (Jordan Journal of Pharmaceutical Sciences, 2025)
This study focuses on Mentha piperita L. cultivated in two regions with distinct bioclimatic levels. The aim is to assess and compare the yield, chemical composition, and pharmacological activities of the plant in these diverse environmental conditions. The phytochemical profile of Mentha piperita L essential oils was established using gas chromatographic analysis. The pharmacological activities were performed in vivo and in vitro using analgesic, anti-inflammatory, antibacterial and antioxidant assays. The optimal yield of essential oil is obtained from the region of Oued Souf with 1.02% and that of the region of Algiers is equal to 0.86%. The GC/MS analysis revealed a richness of the essential oil in Linalool as well as its derivatives linalyl acetate for Oued Souf and linalyl butyrate for Algiers. In all pharmacological activities, the essential oil of Mentha piperita L from Oued Souf region was significantly more potent than essential oil from Algiers. This study can contribute to the application of Mentha piperita L essential oil in the pharmaceutical industry as a promising natural reservoir of volatile compounds with noteworthy therapeutic properties.